Tyro3 upregulation is associated with muscle involvement in patients with idiopathic inflammatory myopathies - Huan Liu; Ying Ren; Qianwei Li; Yanjun Si; Yuehong Chen; Min Dong; Geng Yin; Qibing Xie (Immunologic Research, 2025)

Divergent Flowering Time Responses to Increasing Temperatures Are Associated With Transcriptome Plasticity and Epigenetic Modification Differences at FLC Promoter Region of Arabidopsis thaliana - Yu Han; Li Liu; Mengyu Lei; Wei Liu; Huan Si; Yan Ji; Qiao Du; Mingjia Zhu; Wenjia Zhang; Yifei Dai; Jianquan Liu; Yanjun Zan (Molecular Ecology, 2025)
Understanding the genetic, and transcriptomic changes that drive the phenotypic plasticity of fitness traits is a central question in evolutionary biology. In this study, we utilised 152 natural Swedish Arabidopsis thaliana accessions with re‐sequenced genomes, transcriptomes and methylomes and measured flowering times (FTs) under two temperature conditions (10°C and 16°C) to address this question. We revealed that the northern accessions exhibited advanced flowering in response to decreased temperature, whereas the southern accessions delayed their flowering, indicating a divergent flowering response. This contrast in flowering responses was associated with the isothermality of their native ranges, which potentially enables the northern accessions to complete their life cycle more rapidly in years with shorter growth seasons. At the transcriptome level, we observed extensive rewiring of gene co‐expression networks, with the expression of 25 core genes being associated with the mean FT and its plastic variation. Notably, variations in FLC expression sensitivity between northern and southern accessions were found to be associated with the divergence FT response. Further analysis suggests that FLC expression sensitivity is associated with differences in CG, CHG and CHH methylation at the promoter region. Overall, our study revealed the association between transcriptome plasticity and flowering time plasticity among different accessions, providing evidence for its relevance in ecological adaptation. These findings offer deeper insights into the genetics of rapid responses to environmental changes and ecological adaptation.

Scalable, flexible, ultra-strong, free-standing papery all carbon nanotube membrane with excellent separation and antifouling properties - Yang Yang; Yuhang Cheng; Si Ling; Yanjun Wan; Zhu Xiong; Chunhong Li; Jiangyan Lu; Li Yu; Gaosheng Zhang; Shuaifei Zhao (Chemical Engineering Journal, 2024)